‘Cool' or ‘hot' rational choices: an examination of traits and states in sexual crimes - Pedneault, Amelie (Psychology, crime & law, 2025)
We test Van Gelder and colleagues’ revision to rational choice theory by incorporating traits and states in sexual crime decision models. We studied the index sexual offenses of a sample of 871 male individuals and account for the influence of traits (impulsivity and aggression) and states (age, stressors, alcohol/drugs, and sexual arousal) on their crime decisions. We found that traits and states were associated with use of force, corresponding to ‘hot’ decision making, while ‘cool’ decisions occurred in earlier crime decisions, indicating the importance of decision temporality. Traits and states were not related to immediate crime outcomes. They appear to act as heuristic devices that simplify decision making in the criminal context, without impeding reaching the desired outcomes. There is theoretical value in adding traits and states to traditional rational choice crime models.